Unmet Need for Family Planning: A Challenge to Public Health - Veena V; Holla, Ramesh; Parasuramalu B G; Balaji R (National Journal of Community Medicine, 2014)
Introduction: Unmet need for family planning refers to gap between some women’s reproductive intention and their contraceptive behaviour. This poses a challenge to the family planning programme. Objectives: To find out the extent of unmet need, associated socio-demographic factors and possible reasons for unmet need among pregnant women. Methods: A descriptive cross-sectional study was conducted among 523 pregnant women attending antenatal clinic of Primary health center attached to a medical college in Bangalore for a period of 7 months using pretested semi-structured questionnaire by interview. Descriptive statistics was used for summarization of the data. Statistical association was determined using chi-square test. Results: In the present study the extent of unmet need among pregnant women was 122(23.3%), 99(19.0 %) for spacing the birth and 23(4.3%) for limiting the birth. Unmet need was significantly associated with socio-economic status, number of living children. The main reason for unmet need for family planning was opposition by family members (n=59, 48.3%). Conclusion: The study found that women cited a range of reasons that prevented them from using contraceptives. To address these issues needs various measures like imparting proper family planning education by conducting awareness programmes at the community level, removing misconceptions regarding family planning etc.